Conversor boost aplicado a correção do fator de potência em fontes de alimentação chaveada - MARTINS, Wallison Richard de Abreu (2018)
The work deals with the study of the application to a DC-DC converter, Boost type, for correct the power factor in switched power supplies. Use of this converter as pre-regulator circuit (PFC), originates a high quality rectifier, which aims to ensure the power factor of the source close to unity, the attenuation of injecting harmonic current in the electric grid, and the regulation of the output voltage for a power range specified. From the idealization this circuit as a virtual prototype, simulations were performed in order to analyze it and check its performance compared to conventional rectifiers. We opted for the operation of the converter in continuous conduction mode (CCM), and control for average current, made by IC UC3854, which is also responsible for regulating the output voltage. In general, in this work the steps and modes of operation of the converter, a description of the integrated circuit used, the dimensioning of components, besides of assembly the virtual prototype, the tests performed and the results obtained will be presented.